Study of Coating Geometries and Photoluminescence Properties of Metal Nanoparticles/Graphite Composites. (17th April 2014) - Barone, Pasquale; Barberio, Marianna; Stranges, Fabio; Xu, Fang
Abstract : In this work we present the results of a study of growth and characterization of metal nanoparticles (Ag, Au, and Co)/carbon surfaces. The nanoparticles grew by laser ablation technique and their dimensions were controlled by light scattering study and AFM microscopy before their insertion on graphite surface. Nanoparticles appear randomly disposed on carbon surfaces aggregating to form big particles only in the case of silver. The different behavior of metal nanoparticles on carbon surface was explained in terms of different metal wetting of surface, in agreement with previous theoretical results of He et al. Chemical information, obtained by X-ray photoelectron spectroscopy, indicated that the doping process is a simple physisorption while the interfacial interaction between particles and carbon layers causes local defects in graphite structure and the appearance of a strong photoluminescence signal for all composites. Moreover, the visible optical absorption decreases about 10% indicating the progressive metallization of carbon surface.